AN INTERDISCIPLINARY APPROACH TO ECONOMIC AND HEALTH LAW IN THE PROTECTION OF CHILDREN WHO COMMIT PETTY THEFT: A LITERATURE REVIEW - Gunawan Widjaja (RADJA PUBLIKA, 2025)
This study aims to analyse the interdisciplinary approach of law, economics, and health in the protection of children who commit petty theft through a literature review. The protection of children as perpetrators of minor crimes requires the application of the principles of restorative justice and diversion as stipulated in the Juvenile Criminal Justice System. However, economic factors such as poverty and social inequality are often the main drivers of children committing petty theft, so interventions in the form of economic empowerment and social assistance are urgently needed. In addition, health aspects, particularly the mental and psychological health of children, must also be a primary concern in protection and rehabilitation efforts. The results of the study show that synergy between a humanistic legal system, appropriate economic intervention, and comprehensive health services is very important to ensure optimal protection for children who commit petty theft and to prevent recidivism. Cross-sector collaboration and regulatory strengthening are key to the successful implementation of fair and sustainable child protection.